Acute effects of hyperglycemia in a chemical-genetic ablation model - Howell, Julia (My University, 2016)
Diabetes Mellitus (DM) is a debilitating disease characterized by elevated blood glucose levels, known as hyperglycemia. Glucose, the energy source for metabolism, is transported to the cells of the body by the hormone insulin. Without the proper formation and utilization of insulin, DM occurs in two forms; Type I DM is characterized by the loss B-cells which produce insulin, whereas, Type II DM is characterized by insulin resistance in which the body does not respond to the insulin that is produced. Regardless of DM subtype, 50% of patients suffer with mild to severe forms of nerve damage known as diabetic peripheral neuropathy (DPN). In the quest for therapeutic techniques, we are first trying to determine if zebrafish are an appropriate model organism for studying DPN as they are easier to observe than other animals such as mice, rats and humans. Their ability to serve as an appropriate model is dependent on them showing signs of peripheral nerve damage, as seen in humans, when rendered hyperglycemic. This was examined by exploiting a transgenic zebrafish line, Tg(ins;rifsB-mcherry). In this line, insulin producing B-cells of the pancreas are destroyed using the prodrug metronidazole (MTZ) and visualized by the fluorescent protein, mcherry, which was inserted into its genome. To assess possible peripheral nerve changes, we crossbred the transgenic lines, Tg(nkx2.2a;megfp) and Tg(nbt;dsred), into the Tg(ins;rifsB-mcherry) line to allow us to visualize the perineurial glia (GFP), the motor axons (DsRed) and the B-cells (mcherry) in the offspring. The offspring were raised for 5 days post fertilization (dpt) in egg water and then treated with MTZ for 48 hours. Using epiflourescent microscopy, peripheral nerve disruption was observed in two ways; (1) fewer motor nerves had perineurium (connective tissue that is important in maintaining the integrity of nerves) associated with them and (2) when the perineurium was present, it often appeared to improperly wrap the motor nerve. In addition, the motor axons of the MTZ-treated group also appear to be defasciculated and the neuromasts, mechanosensory hair cells, appear unhealthy compared to the control. This suggests that the sensory and motor systems of zebrafish are influenced by acute hyperglycemia. Future work will include a small molecule drug screen that may be able to provide insight on the molecular mechanisms underlying hyperglycemia induced degeneration of the peripheral nerve.
Keywords: Diabetes mellitus; Hyperglycemia